2017
DOI: 10.4274/jcrpe.3682
|View full text |Cite|
|
Sign up to set email alerts
|

The Relationship between Serum Zonulin Level and Clinical and Laboratory Parameters of Childhood Obesity

Abstract: Objective:To investigate the relationship between zonulin levels and clinical and laboratory parameters of childhood obesity.Methods:The study included obese children with a body mass index (BMI) >95th percentile and healthy children who were of similar age and gender distribution. Clinical (BMI, waist circumferences, mid-arm circumference, triceps skinfold, percentage of body fat, systolic blood pressure, diastolic blood pressure) and biochemical (glucose, insulin, lipid levels, thyroid function tests, cortis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 32 publications
(46 reference statements)
4
29
2
1
Order By: Relevance
“…However, circulating zonulin was below the limit of detection (8.6 ng/mL). This observation may be associated with high variability of zonulin concentration which at least partially may be modulated by inflammation or obesity . In this study, there was no association between claudin‐3 and BMI in patients as well as control group.…”
Section: Discussioncontrasting
confidence: 51%
“…However, circulating zonulin was below the limit of detection (8.6 ng/mL). This observation may be associated with high variability of zonulin concentration which at least partially may be modulated by inflammation or obesity . In this study, there was no association between claudin‐3 and BMI in patients as well as control group.…”
Section: Discussioncontrasting
confidence: 51%
“…Obesity and its complications, including high cholesterol, type 2 diabetes (T2D), coronary heart disease, high blood pressure, and stroke, have been shown to be associated with chronic inflammation 106-108 and frequently linked to alteration of the zonulin pathway, and more than 30 articles have been published on this topic. Several of these studies have shown elevated serum zonulin levels increased in obese versus non-obese subjects [79][80][81][82][83][84][85][86] , and there is evidence of a correlation between total bacteria and serum zonulin levels, suggesting that the gut microbiota may cause increased zonulin levels, and subsequent abnormal gut permeability to endotoxin and ultimately micro-inflammation has been reported in obesity 106 . A recent report also showed that zonulin serum correlates with total calorie, protein, carbohydrate, sodium, and vitamin B 12 intake in obese women, and Ruminococcaceae and Faecalibacterium were more abundant in the low-zonulin group, suggesting that butyrate-producing gut bacteria such as Faecalibacteria could decrease gut permeability by decreasing zonulin levels and lower inflammation 87 .…”
Section: Metabolic Disordersmentioning
confidence: 99%
“…Increased serum/plasma zonulin levels have been described in celiac disease [3] , type 1 and 2 diabetes [4] , [5] or in obesity-associated insulin resistance [6] , [7] ; and circulating plasma zonulin has been suggested as a potential marker of intestinal permeability [8] , [9] , [10] . However, there is insufficient information about zonulin's participation in some important states of intestinal inflammation (e.g., inflammatory bowel diseases, IBD), and there is ambiguous information about serum and fecal zonulin in IBD [11] .…”
Section: Introductionmentioning
confidence: 99%